2015
DOI: 10.1111/echo.12987
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Dysfunction Assessed by Two‐Dimensional Speckle Tracking Echocardiography in Patients with Impaired Left Ventricular Ejection Fraction and Sleep‐Disordered Breathing

Abstract: LA dysfunction and remodeling assessed using 2DSTE in patients with impaired systolic LV function, and IHD is influenced by the severity of sleep apnea independently from LV function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
(64 reference statements)
0
6
0
1
Order By: Relevance
“…Speckle tracking echocardiography (STE), developed for the analysis of left ventricular deformation imaging, 3 allows even the evaluation of left atrial function determining the longitudinal deformation of its myocardial fibers. 4 Normal values and feasibility of this methodic have been already defined for the study of left atrium. 5 Recently, peak atrial longitudinal strain (PALS) determined by STE has demonstrated to be more accurate than E/E' to estimate pulmonary wedge pressure in patients with advanced heart failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speckle tracking echocardiography (STE), developed for the analysis of left ventricular deformation imaging, 3 allows even the evaluation of left atrial function determining the longitudinal deformation of its myocardial fibers. 4 Normal values and feasibility of this methodic have been already defined for the study of left atrium. 5 Recently, peak atrial longitudinal strain (PALS) determined by STE has demonstrated to be more accurate than E/E' to estimate pulmonary wedge pressure in patients with advanced heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Speckle tracking echocardiography (STE), developed for the analysis of left ventricular deformation imaging, allows even the evaluation of left atrial function determining the longitudinal deformation of its myocardial fibers . Normal values and feasibility of this methodic have been already defined for the study of left atrium …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already proved the usefulness of LA STE in sinus rhythm (12, 18) and in AF (19, 20). LA strain has been shown to have additive value for the risk stratification of embolism and post-stroke mortality (20).…”
Section: Introductionmentioning
confidence: 99%
“…Classically, elevated LA pressure is attributed to a noncompliant LV, however we now know that there is a certain amount of atrial noncompliance involved. 23 Recent data suggest a higher risk of atrial fibrillation and atrial fibrillation recurrence in those with poorly compliant left atria. 24 Even though the shunt is left to right, the amount of flow getting to the left atrium via the pulmonary veins is increased.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, patient #3's PCWP decreased from 18 to 10 mm Hg and Qp:Qs dropped from 1.9 to 1.4. Classically, elevated LA pressure is attributed to a noncompliant LV, however we now know that there is a certain amount of atrial noncompliance involved . Recent data suggest a higher risk of atrial fibrillation and atrial fibrillation recurrence in those with poorly compliant left atria .…”
Section: Discussionmentioning
confidence: 99%